Letter - Brook, Charles Wortham, 1901-1983
041-0176-001 SPANISH MEDICAL AID COMMITTEE President: Dr. CHRISTOPHER ADDISON Chairman: Dr. H.B. MORGAN Treasurers: Viscountess HASTINGS Professor MARRACK Viscount CHURCHILL Hon. Secretary: Dr. CHARLES BROOK, L.C.C. 24 NEW OXFORD STREET W.C.1 Telephone: HOLborn 0605 20th August 1936. Sir Walter Citrine, K.B.E., 63, Kingsway, Wembley Park. Dear Sir Walter, We have now completed our arrangements for the departure of the unit on Sunday next. They will leave Victoria at 8.20 p.m. but in order to avoid any confusion at the station we have arranged for the members of the unit, the members of the committee and other friends to be at the Trade Union Club, 24, New Oxford Street, W.C. at 7 p.m. and we shall leave the club at about 7.15 and proceed by motor vehicles to Victoria. Special platform passes will be distributed at the club before leaving. I shall be very grateful to know whether you will as General Secretary of the Trade Union Congress, say a few words of farewell to the unit at the station, and we shall be pleased to know whether you can meet us at the club so that you can accompany the unit to the station. If you are unable to be present perhaps you will be good enough to nominate a deputy. Yours sincerely, Charles Brook Hon. Secretary. 292/946/41/176